MOFs as Environmentally Friendly Photocatalysts for Organic Pollutants Degradation - Hussain, Sajad; Aslam, Muhammad Anis (New Environmentally-Friendly Materials, 2022)
Metal–organic frameworks (MOFs) have gained significant attention as advanced photocatalysts for the degradation of organic pollutants due to their unique structural versatility, high surface area, tunable porosity, and customizable metal–ligand coordination. This review highlights the environmental challenges posed by persistent organic contaminants and the shortcomings of conventional treatment methods. It emphasizes photocatalysis as a sustainable alternative to the currently used methods. The principles of MOF-photocatalysis, including light absorption, charge separation, and the formation of reactive oxygen species, are discussed, along with factors affecting performance, such as pH, temperature, light source, and pollutant type. MOF classes, composites, and hybrids are also investigated as methods to increase photocatalytic performance, stability, and recyclability. There are case studies of the degradation of dyes, phenolics, pharmaceuticals, and pesticides. The aspects of environmental sustainability, such as environmentally friendly synthesis, non-toxic constituents, and life-cycle, are also discussed. Lastly, future research areas and present challenges are described, supporting the idea that MOFs have great potential as an efficient and environmentally friendly tool to fix the problem of water pollution.